Issues of the Development of Pedagogical Education on the Pages of Domestic Ecclesiastical Periodicals (Mid-80s - the First Half of 90s of the Nineteenth Century) - Tetiana Tverdokhlib (Pedagogical Discourse, 2018)
Taking into account the necessity to reform pedagogical training in modern educational institutions of Ukraine, creative actualization of certain ideas on the development of pedagogical education presented on the pages of domestic ecclesiastical periodicals (mid-80s – the first half of 90s of the nineteenth century) is needed. Pedagogical education in the study is revealed as a system of training pedagogical and scientific and pedagogical staff for educational institutions of all types and as a professional training of future priests to the religious and moral upbringing of the flock.The coverage of the issue of pedagogical education development on the pages of such journals as «Pravoslavnyj sobesednik», «Pravoslavnoe obozrenie», «Bogoslovskij vestnik», «Cerkovnyj vestnik», «Volynskie eparhial'nye vedomosti», «Cerkovno-prihodskaja shkola» in the period under research has been considered in the article on the basis of analysis of primary sources. The issue mentioned was developed by M. Shcheglov, N. Poletayev, A. Gusev, A. Govorov, A. Rozhdestvin and others. It has been established that the problems of the development of pedagogical education in the articles of these teachers and theologians were considered only in educational institutions of the Orthodox Church. It has been found out that there was a significant reduction in the thematic range of issues related to pedagogical education in the educational institutions of the ecclesiastical department in the mid 80s - the first half of the 90s of the nineteenth century compared with the second half of the 60's of the nineteenth century - in 1884. It was concluded that they mainly concerned changes in the content of pedagogical education, its educational and methodological support, the forms of organization of pedagogical training, as well as personnel provision of pedagogical education. The ideas about the content of Homiletics in theological seminaries, namely: reorganization of the content of Homiletics, expansion of the section, which highlights the essence of the church sermon were the most substantiated.